PHYTOCHEMICAL SCREENING OF ETHANOL EXTRACT OF TREMBESI FRUIT SEEDS (Samanea saman) - Saptawati, Tunik; Dayanti, Ema; Rachma, Firstca Aulia; Ovikariani (Science and Community Pharmacy Journal, 2022)
Trembesi (Samanea saman) is a fast-growing plant from Central America and Northern South America. the Trembesi Tree is an easily recognize tree because it has an umbrella-shaped canopy with a canopy diameter greater than its height, the trembesi fruit is blackish-brown when ripe, with seeds embedded in the flesh of the fruit. This study aims to determine the class of compounds contained in the ethanol extract of trembesi fruit seeds extraction by maceration method using 70% ethanol solvent. The analysis uses univariates that present data with calculation results. The extract results were obtained by weight of 91% with an amendment value of 18.20%. The phytochemical screening were carried out with color tests and emphasized by the TLC test. The trembesi fruit seed ethanol extract containing alkaloid, flavonoids, saponins, and tannins compounds.